Harmonization of Cooperative Regulations within the ASEAN Framework: A Legal Review of the Malaysian Copy Study - Ineng Naini; Gusnetti; Enita; Elvina A. Saibi; Ali Ramatni; Yani Maidelwita; Rina Mariyana (Journal of Community Service and Application of Science, 2025)
ASEAN regional economic integration emphasizes the importance of regulatory harmonization across various sectors, including cooperatives. This study aims to examine the suitability and challenges of harmonizing cooperative regulations across ASEAN countries through a legal review of Malaysia's cooperative regulatory system. As a country with a developed cooperative legal framework, Malaysia offers best practices in national cooperative management that can be reflected in strengthening the regional cooperative legal framework. This research method uses a normative qualitative approach with a comparative legal analysis of cooperative legislation in Malaysia and several other ASEAN countries. The study results indicate that despite differences in the legal and institutional structures of cooperatives across ASEAN countries, there is potential room for harmonization through shared fundamental principles, such as economic democracy, member involvement, and business sustainability. These findings support the need for cross-border policy dialogue to formulate ASEAN cooperative regulatory standards that are adaptive, inclusive, and appropriate to local characteristics. Harmonization of cooperative regulations across the ASEAN region is considered strategic in promoting economic integration based on community participation and social justice.